An exploratory study on sexual offender registration System in Malaysia / Asmahani Ismail and Muhammad Syafiq Mat Saad - Ismail, Asmahani; Mat Saad, Muhammad Syafiq (Faculty of Law, 2012)
This project paper discusses the mechanism of the sexual offender registration system and the possible implementation of such a database in Malaysia. It compares the mechanism implemented in different jurisdictions, specifically the United States and the United Kingdom. An analysis of the sexual offender registration system in United Kingdom and the state of California is carried out and comparison of the two systems is made. Reference is made to the statutes from the United Kingdom and the State of California namely the Sex Offender Act 1997, the Megan's Law Act 1996, and the Adam Walsh Act 2006. Due to the differences in implementation in both the United Kingdom and the United States, the result of the implementation also differs. In the United States where the information is easily accessible to the public, this has affected the rate of registration by the offenders. This differs than the implementation in the United Kingdom where the limited access creates more confidence in the convicted offenders to report and update their information for the database.